(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores the image of Cho‘lpon in contemporary Uzbek dramaturgy, emphasizing the tragedy of creativity and freedom. Cho‘lpon, as a poet, thinker, and intellectual of the early 20th century, becomes a central figure through which modern playwrights examine the tension between artistic independence and political oppression. The study analyzes how dramatists portray his inner struggles, moral courage, and commitment to national and cultural values amidst historical adversity. By focusing on Cho‘lpon’s tragic fate, the article highlights broader themes of the artist’s responsibility, the conflict between personal ideals and societal pressures, and the enduring relevance of intellectual freedom in modern Uzbekistan. The dramatization of Cho‘lpon’s life serves not only as a historical reflection but also as a philosophical and ethical commentary for contemporary audiences.